(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The essay analyzes the literary and non-literary articles published in the women’s magazine Žena/The Woman during the Balkan Wars and after the First World War. It examines different ways in which the magazine’s contributors described the role of women in those wars. Three key women’s roles are identified: an idealized woman, a nurse and a “delija girl“. The appropriation of the given and prescribed female roles was a crucial step towards women’s emancipation. After the First World War women demanded their political rights based on the fact that they had participated in the war and undertook all men’s work while men were in the battlefield.